Questões étnico-raciais e literatura infantil: a busca por práticas pedagógicas antirracistas - Damasceno, Tamires Taiane Sobreiro (Universidade Federal de São Carlos, 2023)
This course conclusion project is a memorial that aimed to search for anti-racist pedagogical practices through children's literature as paradidactic support material. At first, I bring reports of my experiences, which brought me to the present moment and made me understand the importance of ethnic-racial guidelines. In an inside-out process, I resumed important concepts for a better understanding of racism in Brazil and the anti-racist struggle. After recognizing the place where I am inserted, with theoretical support in books on the anti-racist theme and references on pedagogical practices, I analyzed the children's book "Amoras" by Emicida, with the intention of bringing it as a possibility of paradidactic material that contributes in a positive and light way for the construction of black children's self-identification, appreciation of different knowledge, respect for diversity and for the awareness of subjects about the anti-racist struggle.
Ethnic-racial issues and children's literature: the search for anti-racist pedagogical practices
Keywords: Educação; Education; Pedagogical Practices; Praticas Pedagógicas; Literatura Antirracista; Anti-racist Literature; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO